2018
DOI: 10.1051/e3sconf/20184500114
|View full text |Cite
|
Sign up to set email alerts
|

Porous asphalt pavement for traffic noise reduction and pavement dewatering – the pollution problem

Abstract: The paper characterizes the porous asphalt mixture used in pavement construction. This kind of pavement can reduce traffic noise and reduce the slipperiness of the road pavement. The effectiveness of the porous asphalt depends on many design and technological aspects, but especially on the air-void clearance in the pavement layer. The paper includes the results of water permeability research based on laboratory tests of specimens from actual road pavement. The research shows the differences between the contami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Road-traffic noise diminishes the experience of nature and overall quality of life in areas near high-traffic roadways, with established negative impacts on animal life in surrounding areas [64]. As an example, the noise from passenger cars traveling over porous asphalt is about 5 dB lower than that of traditional pavements due to increased acoustic absorption by porous pavements [65]. In this way, implementing low-noise pavement on roadways maintains peace and maximizes belonging in the environment, which supersedes the potential safety benefits of artificially loud noise (e.g., hearing a vehicle coming).…”
Section: Environmental Harmony Of Appearance and Noisementioning
confidence: 99%
“…Road-traffic noise diminishes the experience of nature and overall quality of life in areas near high-traffic roadways, with established negative impacts on animal life in surrounding areas [64]. As an example, the noise from passenger cars traveling over porous asphalt is about 5 dB lower than that of traditional pavements due to increased acoustic absorption by porous pavements [65]. In this way, implementing low-noise pavement on roadways maintains peace and maximizes belonging in the environment, which supersedes the potential safety benefits of artificially loud noise (e.g., hearing a vehicle coming).…”
Section: Environmental Harmony Of Appearance and Noisementioning
confidence: 99%
“…For the most common applications of pervious pavements, low traffic roadways, walkways, and parking lots, several examples of decades-long durability have been documented across different types of pervious pavements [17,46]. As an example, a U.S. EPA study found porous asphalts to have lower freeze/thaw stress than conventional pavement, potentially leading to a doubling of service life from 15 to 30 years (in continental or polar climates) [65]. Regarding discontinuous surfaces in polar zones, certain interlocking paving systems have been shown to tolerate snow plowing equipment [61].…”
Section: Durability In Operating Environmentmentioning
confidence: 99%